Análise de eficiência do Programa Aquisição de Alimentos para o território de Andradina e Noroeste Paulista - Carvalho, Jaqueline Bonfim De [UNESP]; Modenese, Valéria Da Silva [UNESP]; Sant'ana, Vanessa Zaffani [UNESP]; Sabbag, Omar Jorge [UNESP] (My University, 2016)
This article analyzes the Food Acquisition Program (PAA) modality CPR - Donation with reference to the year 2012, in the municipalities belonging to Andradina territories and São Paulo northwest, using the methodology DEA (Data Envelopment Analysis). In the analysis were used as inputs the resources provided by the program to producers by municipality (R$) and the number of suppliers (producer) and as outputs the amount of feed delivered (Kg) and the number of consumers (consumer entity). The results show that only 21.43% of the municipalities work on efficient scale, with optimal levels of inputs and outputs.
Efficiency analysis of the food acquisition programme to the territory of Andradina and São Paulo northwest
Keywords: Commercialization; Performance; Public policies; Socioeconomics